Artificial Intelligence in the Construction Industry in India: Opportunities, Challenges & Future Prospects (International Journal of Latest Technology in Engineering Management & Applied Science, 2026)
The construction industry in India, a key driver of economic growth contributing significantly to GDP and employment, faces persistent issues such as project delays, cost overruns, labour shortages, safety concerns, and low productivity. Artificial Intelligence (AI) offers transformative potential through applications in project management, predictive analytics, design optimization, risk assessment, safety monitoring, and supply chain management. With 54% of Indian construction firms already adopting AI and ML as of recent reports, India leads in digital adoption within the sector regionally. Supported by government initiatives like the National Strategy for Artificial Intelligence and the India AI Mission, the sector is poised for rapid growth. This paper examines key opportunities, major challenges, and future prospects, highlighting pathways for sustainable and efficient infrastructure development.